Highly sensitive composite electrode based on electrospun carbon nanofibers and ionic liquid - Liu, Yang; Wang, D.; Huang, J.; Hou, H.; You, T. (Elsevier Inc., 2010)
A novel composite electrode has been developed using electrospun carbon nanofibers (CNF) and the ionic liquid 1-butyl-4-methylpyridinium hexaflurophosphate (PFP). The highly pure CNF without any pretreatment exhibited very low background noise and high voltammetric responses. When applied to sensing of biomolecules under physiological conditions, the CNF/PFP electrode provided attractive electrochemical performances, such as high sensitivity and good selectivity for simultaneous detection of dopamine, ascorbic acid and uric acid, guanine and adenine, as well as high signal-to-noise ratio and good stability for amperometric detection of NADH.